PENGEMBANGAN MEDIA VIDEO TUTORIAL UNTUK MENINGKATKAN HASIL BELAJAR DAN SIKAP POSITIF PADA MATA KULIAH MULTIMEDIA PRESENTASI - Vidya Pratiwi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
The research is motivated learner development of instructional media and optimizing less difficulty understanding the material learners, learners are reluctant to provide explanations over and never develop practical learning media. It aims to produce multimedia presentations tutorial video media to enhance learning outcomes and positive attitude of students. The subject of his research, validation to the matter experts and instructional media expert. Further trials are held as many as 3 individual, small group testing as many as 13 people, and a large group trials as many as 46 people. Test results of the feasibility study used instrument validity and reliability testing with a sample test of 20 questions. Attitude instrument used due diligence test validity and reliability testing with a sample test of 30 questions. The data obtained through respondents using a questionnaire enclosed and measured using a Likert scale and percentage. Analysis of trial data using paired samples t test to analyze differences in learning outcomes in the experimental class and the control class. The results of this study are as follows: The results of the analysis of the improvement of learning outcomes; different test post-test control class and experimental class with a level of sig 0.000 <0.05 there is a difference. The results of the analysis of attitudes, students who gave a negative attitude and a positive attitude 9 persons 14 persons. Development of video tutorials media has a positive influence on the improvement of learning outcomes and positive attitude of students. Media feasible to use video tutorials to students who take courses multimedia presentations. Further advice from the researchers: Using video tutorials media products need to be used to improve learning outcomes in particular multimedia presentations oint hyperlinks, embedding and distribution of presentation. At such material learners can understand in detail the steps of manufacture. It is recommended to the learner in order to take advantage of video tutorials media so that learners are able to solve the difficulty to understand the material